Online/offline evolutionary algorithms for dynamic urban green space allocation problems. Issue 4 (4th July 2017) - Vallejo, M.; Corne, D.; Vargas, P.
Abstract : Urban-planning authorities continually face the problem of optimising the allocation of green space over time in developing urban environments. The problem is essentially a sequential decision-making task involving several interconnected and non-linear uncertainties, and requires time-intensive computation to evaluate the potential consequences of individual decisions. We explore the application of two very distinct frameworks incorporating evolutionary algorithm approaches for this problem: (i) an 'offline' approach, in which a candidate solution encodes a complete set of decisions, which is then evaluated by full simulation and (ii) an 'online' approach which involves a sequential series of optimisations, each making only a single decision, and starting its simulations from the endpoint of the previous run. We study the outcomes, in each case, in the context of a simulated urban development model, and compare their performance in terms of speed and quality. Our results show that the online version is considerably faster than the offline counterpart, without significant loss in performance.